OTVORENA REPARACIJA ANEURIZME AORTE U ENDOVASKULARNOJ ERI - Matejević, David (Medical Research, 2022)
Open repair (OR) of aortic aneurysms is still relatively mutilating and risky in older and high-risk patients. Since the introduction of EVAR, significantly lower perioperative mortality has been noted. Besides advantages, endovascular treatment also has disadvantages, due to which OR still has very important role in the endovascular era. In vast majority of the patients younger than 65, with good overall condition, long life expectancy and favourable anatomy, as well as in patients with hostile aneurysm neck anatomy, heritable connective tissue disorders, complete thrombosis of abdominal aortic aneurysm (AAA) and potent accessory renal arteries, OR is the first treatment option in comparison to endovascular treatment. EVAR is recommended as the first treatment option in patients with inflammatory aneurysms and OR should be considered only in better shaped patients with inflammatory AAA and significant hydronephrosis. Late open surgical conversion (LOSC) is a noted event after endovascular tretment and is associated with significantly higher perioperative mortality and other serious perioperative complications in comparison with primary OR. Multicenter randomized controlled trials (RCT) did not find significant difference regarding 30-day mortality between open and endovascular repair of ruptured AAA. However, not all ruptured AAA are suitable for endovascular repair. In hemodynamically unstable patients, when there is no time for MDCT angiography, EVAR is not possible and OR is the only option. The incidence of abdominal compartment syndrome after OR is significantly lower in comparison to EVAR thanks to surgical evacuation and drainage of retropertoneal hematoma. The improvement of results of aortic aneurysm treatment is largely dependent on the volume of yearly aortic operations. Having in mind all the mentioned advantages and disadvantages of OR and endovascular repair, we can conclude that in high volume centers, younger generations of vascular surgeons should be educated in standard and complex open aortic surgery.